Book Review of Educational Opportunity in Rural Contexts: The Politics of Place - Daniella Hall (Journal of Research in Rural Education, 2016)
Within the complex field of education policy, rural schools and communities are all too often left out of the primary discourse. Education initiatives, policies, and funding systems are typically designed for the majority - suburban or urban communities - and lack necessary modifi cations to best meet the needs and priorities of rural education systems (e.g., Kannapel & DeYoung, 1999). Johnson and Zoellner note, "It is important to point out that policymakers often do not intend harm to rural schools; it is their ignorance of the unique assets and challenges of rural schools and communities that results in the unintended and often harmful policy outcomes," (2016, p. 6). This ignorance is not solely attributable to inattentive policymakers, however. Research on rural education policy has not kept up with current political demands; over the past ten years, fewer than a dozen U.S. policy-specifi c pieces have been published in the Journal for Research on Rural Education.